2016
DOI: 10.1155/2016/2904832
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Drug Susceptibility Patterns ofMycobacterium tuberculosisComplex Strains Responsible of Human Pulmonary Tuberculosis in the Major Rearing Region in Cameroon

Abstract: Background. Cameroon this last decade continues to present a low contribution of M. africanum and M. bovis in human tuberculosis (TB), while M. bovis was prevalent in cattle but all these pieces of information only concerned West and Center regions. Methods. We carried out the first study in Adamaoua, one of the most rearing regions of Cameroon, on the genetic structure and drug susceptibility of the MTBC strains isolated from newly diagnosed sputum smear-positive patients aged 15 years and above. For that pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Two previous studies reported LAM10 SIT 61 (Cameroon) 34 , 36 , albeit a very low prevalence. This clade originates from Africa and has been associated with drug resistance in Cameroon 38 . Its occurrence in our setting may be related to recent transmission due to migration from Africa, but other evidence links the occurrence of African TB strains in Brazil to the slave trade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies reported LAM10 SIT 61 (Cameroon) 34 , 36 , albeit a very low prevalence. This clade originates from Africa and has been associated with drug resistance in Cameroon 38 . Its occurrence in our setting may be related to recent transmission due to migration from Africa, but other evidence links the occurrence of African TB strains in Brazil to the slave trade.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that biological differences among the circulating strains in our setting may impact the genetic distribution of M. tuberculosis and consequently favor resistance within some clades. In this regard, the Cameroon family is described as presenting genetic features that may cause alterations in pathogenic behavior, e.g., changes in metabolic pathways due to insertion elements (IS) in genes involved in physiological processes 38 . The possibility that such changes may confer a selective advantage deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, isolates clustered with spoligotyping as L4.6.2/Cameroon/SIT61 were partially resolved in six clusters by 24 variable number tandem repeat. 26 L4.6.2/Cameroon/SIT61, and the L4.6.2/Cameroon sublineage in general (spoligotyping signature lacking spacers 23–25 and 33–36) have been reported to be the main genotypic lineage in other Nigerian states (39.5% in Cross River 36 and 66% in Ibadan) 37 and in neighboring countries (66% in Cameroon, 38 33% in Chad, 39 33% in Benin, 40 and 30% in Burkina Faso). 41 The spread of this family could be associated with recent transmission of TB.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Recent results from our team based on spoligotyping performed directly on sputum smears extracts show that M. africanum West African 1 is geographically constrained to a limited number of regions in South-East Nigeria and likely associated with specific populations. 42 On the contrary, the prevalence of M. africanum is highly variable in different regions of Africa (3% in Cameroon 38 and 20% in Ghana) 43 with a decreasing trend in transmission over the last three decades. 44 Research is needed to determine the mechanism(s) underlying the putative decreasing trend of M. africanum and the increasing selection and dissemination of the Cameroon sublineage in certain parts of Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of M. tuberculosis in animal has been also described [8,[29][30][31]. The M. tuberculosis lineage SIT 53 has been more descript in human TB in Cameroon but never in cattle, goat, pig or sheep [8,[32][33][34][35]. Knowing that human remain the true host for M. tuberculosis, the finding of M. tuberculosis in sheep may traduce an indirect zoonosis case as it has been suggested for cattle [8].…”
Section: Discussionmentioning
confidence: 99%